Invisiblizing Trans Homelessness: The Prefiguration of Cis Homelessness through Homelessness Counts - Withers, A.J. (Atlantis, 2024)
Municipalities in Canada routinely count unhoused populations to inform policy and services. By examining 165 English Canadian municipal homeless count reports, this article explores how trans, Two Spirit, and nonbinary (T2SNB) people, and sex and gender more broadly, are constructed. Homelessness is prefigured as cis within and through the counting and reporting methodology and text. In subsequent counts, homeless services—including new and revamped services based on prior counts—are used to locate homeless people to count thus intensifying the construction of and further prefiguring cis homelessness. The gender binary is both overtly and subtly upheld through these reports in many municipalities. It is argued that there can be substantial material consequences for the invisibilization and misrepresentation of T2SNB people that can impact available services and housing.